IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH CROSSWORD PUZZLE GAME TO THE EIGHTH GRADE STUDENTS OF SMP SWASTA DHARMA BAKTI MEDAN - Manullang, Unita; Lumban Raja, Viator; Sari, Anna Stasya Prima (Kairos English Language Teaching Journal, 2020)
This research is aimed to improve students’ vocabulary mastery through the application of crossword puzzle game. The subject of this research of the eighth grade students of SMP Swasta Dharma Bakti Medan. This research was conducted by applying Classroom Action Research (CAR) which was performed in two cycles (cycle I and cycle II) and each cycle consisted of three meetings. This instrument of collecting data are quantitative (vocabulary test) data and qualitative data (diary notes, observation sheet and photograph evidences).the result of vocabulary test as the quantitative data show that mean of students’ score increased continuously from pre-test 36,71, post-test in cycle I 64.10, to post-test cycle II 78,48. The diary notes, observation sheet and photograph evidences as qualitative data showed that the teaching and learning process ran well. It was found that crossword puzzle game could improve students’ vocabulary mastery. It is suggested that teachers of English should apply crossword puzzle game as one of the game in teaching vocabulary mastery.